2019
DOI: 10.1038/s41598-019-42478-2
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Preserves Physiological Arousal in Emotional Memory

Abstract: Traumatic experiences are associated with increased emotional arousal. Overnight consolidation strengthens the episodic content of emotional memories, but it is still unclear how sleep influences the associated arousal response. To investigate this question, we compared the effects of sleep and wake on psychophysiological and subjective reactivity during emotional memory retrieval. Participants provided affective ratings for negative and neutral images while heart rate deceleration (HRD) and skin conductance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…17,29 These efforts are deliberate and conscious, which require the involvement of cognitive and intellectual functions, thereby increasing the mental and emotional arousal levels, decreasing the sleep quality. 30,31 The present study was a cross-sectional one. Therefore, it is important to examine the effects of independent variables on sleep disorders in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…17,29 These efforts are deliberate and conscious, which require the involvement of cognitive and intellectual functions, thereby increasing the mental and emotional arousal levels, decreasing the sleep quality. 30,31 The present study was a cross-sectional one. Therefore, it is important to examine the effects of independent variables on sleep disorders in longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also complement a broader literature, where selective sleep-associated memory effects are not always replicated. For example, emotionally salient information is widely considered to be particularly sensitive to consolidation during sleep [47], but many studies have failed to find a preferential impact of sleep on emotionally negative relative to neutral memories [6,[26][27][28][29]48]. To what extent, and under what conditions, sleep offers selective benefits to memory is therefore still largely unknown.…”
Section: Plos Onementioning
confidence: 99%
“…However, other findings concerning the selective influences of sleep have been somewhat contradictory. A number of studies have failed to observe a preferential benefit of sleep on emotionally negative relative to neutral memories [6,[25][26][27][28][29][30], and others have observed no impact of monetary reward on sleep-associated consolidation [31][32][33]. In recent work, knowledge of a future test had no impact on the overnight retention of declarative or nondeclarative memories [34], and failed to influence the neural correlates of memory retention after sleep [35].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mounting evidences suggest sleep preferentially consolidates emotional memories and makes them long‐lasting (Cox et al., 2018; Hu et al., 2006; Wagner et al., 2001). Besides memories, a few studies suggested sleep may also preserve affective tones of emotional memories, indicated by subjective and physiological responses (Ashton et al., 2019; Baran et al., 2012; Menz et al., 2013; but also see Cox et al., 2018; Cunningham et al., 2014; Van Der Helm et al., 2011 for discrepant findings). Accordingly, one tenable hypothesis is that sleep deprivation in the early aftermath of trauma may alleviate PTSD symptoms, including involuntary intrusions and emotional hyperarousal.…”
Section: Introductionmentioning
confidence: 99%
“…memories, indicated by subjective and physiological responses (Ashton et al, 2019;Baran et al, 2012;Menz et al, 2013; but also see Cox et al, 2018;Cunningham et al, 2014;Van Der Helm et al, 2011 for discrepant findings). Accordingly, one tenable hypothesis is that sleep deprivation in the early aftermath of trauma may alleviate PTSD symptoms, including involuntary intrusions and emotional hyperarousal.…”
mentioning
confidence: 97%